P0482INTERSTITIAL HSP70 EXPRESSION AT DIAGNOSIS ASSOCIATES WITH LONG TERM RENAL SURVIVAL IN AN ANCA VASCULITIS COHORT. (6th June 2020) - Petrakis, Ioannis; Androvitsanea, Ariadni; Stratakis, Stavros; Daphnis, Eugene; Stylianou, Kostas
Abstract: Background and Aims: Heat shock proteins(HSP) present an evolving role in immune response. ANCA associated vasculitis(AAV) is often associated with kidney injury and progression to chronic kidney disease(CKD) Method: Twenty nine patients with biopsy proven renal AAV were followed(1995-2015). Study end point was renal death. Renal tissue at diagnosis was stained with monoclonal antibodies against HSP60 and HSP70. Interstitial inflammatory cells and interstitial fibrosis graded were evaluated as mild(0-50%) or severe(≥50%). Healthy renal tissue served as control. Survival analysis(Kaplan-Meier), Fisher's exact test, or Test Chi-Square and bivariate analysis were performed. Statistical significance was set at <0, 05. Results: Mean age and mean eGFR at baseline was 57, 8±19.2 years and 24, 47 ml/min/1, 73m 2 BSA respectively. Interstitial inflammatory infiltrates were present in most patients. Interstitial fibrosis was present in 10, 3% of patients. Control biopsies showed a weak HSP expression. AAV-patients presented significantly higher HSP expression within crescents, proximal tubule, distal tubule and renal interstitium. Renal fibrosis associated with intense interstitial HSP70 expression(Pearson´s-R=0.521 p=0, 004). Interstitial inflammatory infiltrates associated with increased distal tubular HSP60 expression(Pearson´s-R=0.672 p<0, 001). Renal fibrosis associated with renal function loss(Mean time to renal replacement therapy 2.6 years, 95%CI 1.2-4.1 years, Log-Rank Chi-Square=4.33, p=0.038). Strong interstitial HSP70 expression associated with worsened renal survival in AAV-patients even in the absence of severe renal fibrosis(Mean time to renal replacement therapy initiation 0 years ; 95%CI 0, Log-Rank Chi-Square=11.45, p=0.001). Conclusion: Interstitial HSP70 overexpression is associated with worse renal outcomes in renal AAV. To our knowledge this is the first study that shows an association of renal heat shock protein expression and renal outcomes in an AAV cohort.